A novel component different from endotoxin extracted from Prevotella intermedia ATCC 25611 activates lymphoid cells from C3H/HeJ mice and gingival fibroblasts from humans. - Iki, K (1997)
A novel immunobiologically active fraction was prepared from a phenol-water extract of Prevotella intermedia ATCC 25611 by Sephadex G-100 column chromatography. The fraction consisted mainly of carbohydrate and protein and was devoid of fatty acid. The fraction showed high-molecular-weight bands (10,000 to 12,000) on deoxycholate polyacrylamide gel electrophoresis (DOC-PAGE) and was scarcely active in a Limulus test. We designated the fraction Prevotella glycoprotein (PGP). The PGP fraction showed strong mitogenicity on splenocytes and cytokine-inducing activities on peritoneal macrophages from both C3H/HeJ and C3H/HeN mice, and it stimulated human gingival fibroblasts to produce cytokines. The activities of the PGP fraction were resistant to heat inactivation (100 degrees C for 1 h) and protease treatments and were scarcely inhibited by polymyxin B. In contrast, the purified lipopolysaccharide fraction (LPS-PCP) extracted from the same bacterium with a phenol-chloroform-petroleum ether mixture, which showed strong Limulus activity and a single low-molecular-weight band (approximately 3,000) on DOC-PAGE, lacked the activities on splenocytes and macrophages from C3H/HeJ mice and human gingival fibroblasts. The activities of the LPS-PCP fraction on cells from C3H/HeN mice were completely inhibited by polymyxin B. The LPS extracted from the same bacterium with hot phenol-water (LPS-PW) exhibited the properties of both the PGP fraction and the LPS-PCP fraction. These findings suggest that the unique bioactivities of the LPS-PW fraction of oral black-pigmented bacteria reported to date, which differed from those of the classical endotoxin, were derived from the PGP fraction and not from the LPS itself.